2021
DOI: 10.1002/ijgo.13702
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility preservation: Impact of cancer on ovarian function and oocyte quality

Abstract: Fertility preservation in women with cancer is one of the most debated and current issues in reproductive medicine. The use of lifesaving therapies in these patients negatively affects reproductive function and ovarian reserve, frequently resulting in infertility. 1 One previous study reported that 3% of cancer diagnoses concern patients under the age of 40. 2 Thus, it is important to propose measures for fertility preservation of patients who desire future pregnancies. [3][4][5][6][7] In 2013, the American So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In fact, our univariate and the multivariate analysis identified that cancer is the only risk factor for the presence of dysmorphic oocytes in BC patients. However, these women did not have a compromised ovarian reserve in agreement with the results of several authors [ 6 , 9 , 14 , 29 , 30 ]. In contrast to our results, Quinn et al showed that breast cancer diagnosis is not associated with a decreased maturity rate of retrieved oocytes compared with patients undergoing elective fertility preservation for male factor [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, our univariate and the multivariate analysis identified that cancer is the only risk factor for the presence of dysmorphic oocytes in BC patients. However, these women did not have a compromised ovarian reserve in agreement with the results of several authors [ 6 , 9 , 14 , 29 , 30 ]. In contrast to our results, Quinn et al showed that breast cancer diagnosis is not associated with a decreased maturity rate of retrieved oocytes compared with patients undergoing elective fertility preservation for male factor [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…The clinical features of all the subjects are shown in Table 1 . Only estradiol resulted significantly different ( p < 0.05) in the two groups with lower levels observed in BC women thanks to the administration of aromatase inhibitors (letrozole) in women with hormone-sensitive breast cancer [ 13 ]. No other significant differences in clinical parameters were found.…”
Section: Resultsmentioning
confidence: 99%
“…BC is one of the oncological pathologies for which is indicated fertility preservation [ 7 ], a type of procedure often applied in oncology to give an opportunity to cancer survivors to maintain reproductive health and have children after oncologic treatment [ 8 , 9 , 10 ]. Chemotherapy, radiotherapy, surgery or a combination thereof expose women of reproductive age to risk of damage to the ovary, increase the risks of premature ovarian failure (POF), early menopause, ovarian endocrine disorders, and infertility [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte CLCG is one of the common oocyte morphological abnormalities, and the cause and mechanism of its formation are still unclear (17)(18)(19)(20). Studies revealed that in the natural cycle, the maturation of the oocyte nucleus and cytoplasm often occurs synchronously, but the development of the two may be asynchronous in the ovulation cycle (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%